2011
DOI: 10.3892/ijmm.2011.687
|View full text |Cite
|
Sign up to set email alerts
|

DcR3-TL1A signalling inhibits cytokine-induced proliferation of rheumatoid synovial fibroblasts

Abstract: Abstract. decoy receptor 3 (dcr3), a member of the tumour necrosis factor receptor (tnfr) superfamily, lacks the transmembrane domain of conventional tnfrs in order to be a secreted protein. dcr3 competitively binds and inhibits members of the tnf family, including fas ligand (fasl), liGHt and tl1a. We previously reported that tnfα-induced dcr3 overexpression in rheumatoid synovial fibroblasts (ra-flS) protects the cells from fas-induced apoptosis and that dcr3 induces Vla-4 expression in tHP-1 macrophages to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 21 publications
1
7
0
Order By: Relevance
“…In addition, TNFSF15 expression in PDR epiretinal membranes correlated with the activity of angiogenesis. Our results in PDR are in agreement with previous studies that demonstrated TNFSF15 expression by synovial fibroblasts and mononuclear phagocytes in synovial tissue of rheumatoid arthritis patients [36,37], by endothelial cells and macrophage/foam cells in atherosclerotic plaques [39], by mononuclear and neutrophil infiltration, perivascular spindle-like cells, and endothelial cells in psoriatic skin lesions [38], and by macrophages and CD4+ and CD8+ lymphocytes in intestinal tissue specimens from patients with Crohn's disease [30]. …”
Section: Discussionsupporting
confidence: 83%
See 3 more Smart Citations
“…In addition, TNFSF15 expression in PDR epiretinal membranes correlated with the activity of angiogenesis. Our results in PDR are in agreement with previous studies that demonstrated TNFSF15 expression by synovial fibroblasts and mononuclear phagocytes in synovial tissue of rheumatoid arthritis patients [36,37], by endothelial cells and macrophage/foam cells in atherosclerotic plaques [39], by mononuclear and neutrophil infiltration, perivascular spindle-like cells, and endothelial cells in psoriatic skin lesions [38], and by macrophages and CD4+ and CD8+ lymphocytes in intestinal tissue specimens from patients with Crohn's disease [30]. …”
Section: Discussionsupporting
confidence: 83%
“…Further studies have shown that it is also secreted by monocytes/macrophages, dendritic cells, CD4+ and CD8+ T cells, and synovial fibroblasts [30,36,37,38,39]. Using immunohistochemistry, we demonstrated for the first time that the TNFSF15 protein was specifically localized in vascular endothelial cells, mononuclear cells and myofibroblasts in epiretinal membranes from patients with PDR.…”
Section: Discussionmentioning
confidence: 81%
See 2 more Smart Citations
“…DcR3, a member of the soluble TNF receptor (TNFR) superfamily, sharing a similar sequence with OPG, TNF2, and Fas, can competitively bind to FasL, TL1A, and LIGHT, inhibit apoptosis, modulate immune function, and induce angiogenesis 1719. DcR3 has been found to be highly expressed in many malignant tumors 2023.…”
Section: Introductionmentioning
confidence: 99%